Economic valuation of the environment : methods and case studies - Garrod, Guy.; Willis, K. G. (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 1999)
The increasing demand which society places on the natural environment have led to seeking new ways of estimating the monetary costs of environmental degradation so that they can be compared with the benefits of development. This book provides a comprehensive and readable examination of the major techniques used in cost-benefit analysis and project appraisal to value environmental goods and services.
Includes bibliographical references and index.
nmn, 09/08/16, ijb 09/04/2019
Loan
Keywords: Environmental economics; Environmental auditing